2020
DOI: 10.1016/j.sab.2020.105793
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle enhanced laser induced breakdown spectroscopy of liquid samples by using modified surface-enhanced Raman scattering substrates

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…It was shown, that the material and surface concentration of NPs, as well as the laser wavelength and irradiance all have a great impact on the signal enhancement achievable. 12,550 The production of the plasma plays a crucial role in LIBS. In general, the plasma induction needs the production of free electrons, the so-called seed electrons.…”
Section: Methodology and Applicationsmentioning
confidence: 99%
See 3 more Smart Citations
“…It was shown, that the material and surface concentration of NPs, as well as the laser wavelength and irradiance all have a great impact on the signal enhancement achievable. 12,550 The production of the plasma plays a crucial role in LIBS. In general, the plasma induction needs the production of free electrons, the so-called seed electrons.…”
Section: Methodology and Applicationsmentioning
confidence: 99%
“…550 Modied SERS substrates consisting of Ag NPs on indium-tin-oxide glass were also used for quantitative NELIBS measurements on liquid solutions of Mn, Zn and Cr, and it was found that interparticle distance plays crucial role in efficient enhancement. 12 A biological sample was used as subject in the rst demonstration of the NELIBS effect. A colloidal silver solution was applied to a leaf surface 469 allowing the measurements of several alkaline metals with an enhancement of about a factor of 5.…”
Section: Methodology and Applicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Phages can be used for designing surface-enhanced Raman scattering (SERS) sensors by implementing phage display with the noble metal-binding motif. SERS sensors are usually based on nanostructured silver or gold surfaces [ 167 , 168 , 169 ]. The nanoarchitecture of those metals enhances the electromagnetic field of excitation light, which amplifies the signal from the analyte.…”
Section: Bacteriophages In Materials Sciencementioning
confidence: 99%